Understanding the meaning of Kuchikamizake as a Japanese cultural heritage - Pufiani, Amanda Tiara; Saifudin, Akhmad (Japanese Research on Linguistics, Literature, and Culture, 2024)
Culture is essential because it is the foundation of national character, a reflection of identity, and an ancestral heritage that must be preserved. The critical value of culture reflects the identity and character of a nation, distinguishing it from other countries. Culture is a legacy from ancestors that must be maintained and preserved. One example of traditional culture that is still preserved is kuchikamizake (chewing sake). Kuchikamizake is the forerunner of sake, a traditional Japanese alcoholic beverage. This research is interesting because the kuchikamizake manufacturing process requires virgins to chew the rice that will be made into sake. The manufacturing process is currently considered unhygienic and disgusting. The purpose of this study is to understand the history and meaning of kuchikamizake. The type of research used in this study is qualitative research with a library study method. This study found that kuchikamizake has existed since the Yayoi period in 300-250 BC. The meaning of kuchikamizake is seen as a cultural heritage, a sacred drink related to Shinto rituals, and as a Japanese cultural identity.